2016
DOI: 10.1016/j.foodchem.2015.07.109
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose behenate as a crystallization enhancer for soft fats

Abstract: The addition of sucrose behenate for the modification of the physical properties of soft fats, such as soybean oil-based interesterified fat, refined palm oil, and palm mid fraction was studied. The addition of sucrose behenate was verified to affect the crystalline network of fats, changing the hardness and solids profile. The isothermal crystallization behaviors of the fat blends with 1% sucrose behenate were analyzed at 20 and 25 °C. Temperature had a greater effect on the speed of crystallization (k) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The regiospecific distribution of the samples was determined by high-resolution 13 C nuclear magnetic resonance (NMR) spectroscopic analysis of the TAG acyl chains. The analyses were performed on an NMR spectrometer (Bruker Advance DPX 300; Silberstreifen, Rheinstetten, Germany).…”
Section: Regiospecific Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The regiospecific distribution of the samples was determined by high-resolution 13 C nuclear magnetic resonance (NMR) spectroscopic analysis of the TAG acyl chains. The analyses were performed on an NMR spectrometer (Bruker Advance DPX 300; Silberstreifen, Rheinstetten, Germany).…”
Section: Regiospecific Distributionmentioning
confidence: 99%
“…The analyses were performed on an NMR spectrometer (Bruker Advance DPX 300; Silberstreifen, Rheinstetten, Germany). The determination of 13 C was performed at a frequency of 75.8 MHz with a 5-mm multiple nuclear probe operating at 30°C, as previously reported by Vlahov. [15,16] The results are presented as the compositions of oleic and linoleic acids at the sn-2 and sn-1,3 positions of TAGs.…”
Section: Regiospecific Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem has been solved through the addition of polyglycerol fatty acid esters (PGFEs), mainly due to formation of a liquid-crystal-like supramolecular complex structure containing the high-melting DAG fractions and PGFEs (Saitou et al, 2014;Saitou et al, 2017). Other minor components such as phytosterol esters (Daels, Foubert, & Goderis, 2017), sucrose behenate (Domingues, Da Silva, Ribeiro, Chiu, & Gonçalves, 2016), lecithin (Rigolle et al, 2015), and sugar (West & Rousseau, 2017) have also been reported to adjust the crystallization and melting behavior of fats and oils. It should be noted when SLs (for example, MAGs and DAGs) are added as minor components into a TAG system, they show complex promotion or retardation effect on the crystallization and melting behavior, depending on additive type, addition amount, and bulk oil type (Alfutimie, Al-Janabi, Curtis, & Tiddy, 2016;Da Silva et al, 2017;Da Silva, Domingues, Chiu, & Goncalves, 2017b;Tavernier, Moens, Heyman, Danthine, & Dewettinck, 2019a), which has been extensively reviewed (Patel & Dewettinck, 2015b;Smith, Bhaggan, Talbot, & Van Malssen, 2011) and will not be discussed here.…”
Section: Crystallization and Melting Behaviormentioning
confidence: 99%